Now you see them, now you don’t: performance and the politics of localizing (forced) migration governance in the Horn of Africa’s secondary cities - Kihato, Caroline Wanjiku; Landau, Loren B (SAGE Publications, 2024)
We critically examine a multi-year initiative led by Cities Alliance with municipalities and civil society groups in Somaliland, Kenya, Uganda, and Ethiopia to respond to refugees and migration. Adapting Goffman’s work, we posit that in ambiguous and resource-scarce political environments, network success rests on supporting two “frontstages” and a shared “backstage”. On stage one, authorities “visibilize” refugees to attract funding and national support while shaping national-level norms. On stage two they make refugees “invisible” within their own development strategies, integrating displaced populations into urban planning through data collection, service investments, and inclusive strategies. In an experimental and collaborative backstage, municipal actors share resources and workshop varied scripts for their respective audiences. The initiative has lessened host–refugee tensions, strengthened municipal voices in national and regional policy fora, fostered local accountability, and created financial and bureaucratic resources better able to outlast the vagaries of humanitarian or emergency aid.